2015
DOI: 10.1111/1750-3841.13085
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bacterial Pathogens in Medium and on Spinach Leaf Surfaces using Plant‐Derived Antimicrobials Loaded in Surfactant Micelles

Abstract: Antimicrobial essential oil component (EOC)-containing micelles assist the delivery of natural food antimicrobials to food surfaces, including fresh produce, for decontamination of microbial foodborne pathogens. Antimicrobial EOC-loaded micelles were able to inhibit the enteric pathogens Escherichia coli O157:H7 and Salmonella Saintpaul in liquid medium and on spinach surfaces. However, pathogen reduction generally was not impacted by the method of micelle application (spraying, immersion washing) on spinach s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…At the critical micelle concentration, a surfactant will self‐assemble into thermodynamically favored aggregates, such as micelles and liposomes (McClements, ). Previous studies have shown encapsulation of EOCs in surfactant micelles improved the dispersion of EOCs in aqueous fluids, resulting in improved inhibition of foodborne pathogens in foods, including fresh produce (Kang & Song, ; Park et al, ; Pérez‐Conesa, Cao, Chen, McLandsborough, & Weiss, ; Ruengvisesh, Loquercio, Castell‐Perez, & Taylor, ; Zhang, Critzer, Davidson, & Zhong, ).…”
Section: Introductionmentioning
confidence: 99%
“…At the critical micelle concentration, a surfactant will self‐assemble into thermodynamically favored aggregates, such as micelles and liposomes (McClements, ). Previous studies have shown encapsulation of EOCs in surfactant micelles improved the dispersion of EOCs in aqueous fluids, resulting in improved inhibition of foodborne pathogens in foods, including fresh produce (Kang & Song, ; Park et al, ; Pérez‐Conesa, Cao, Chen, McLandsborough, & Weiss, ; Ruengvisesh, Loquercio, Castell‐Perez, & Taylor, ; Zhang, Critzer, Davidson, & Zhong, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar MICs for other plant-derived antimicrobials against E. coli O157:H7 and other Enterobacteriaceae have been reported elsewhere [ 25 , 26 ]. Previous research has also demonstrated enhanced antimicrobial efficacy of plant essential oil components following micelle entrapment in complex food matrices, reportedly resulting from enhanced dispersion of the hydrophobic oils into the aqueous fraction of the food and transport of essential oil components into the membrane of STEC isolates and other bacterial organisms [ 16 , 18 , 25 , 27 , 28 ]. Refrigerated storage is not expected to have significantly inhibited eugenol release by SDS micelles, given previous reports in which a 4.1 log 10 -cycle reduction of Salmonella Enteritidis was reported during a 5 min exposure to 1% SDS/levulinic acid micelles at 8 °C [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The working stock was stored at 5 ± 1 °C in a foil-wrapped container until ready for use. Following calculation of required eugenol and surfactant for micelle generation [ 16 ], eugenol in alcohol and surfactant in sterile water were mixed and brought to volume with sterile distilled water as required. Mixtures were stirred at room temperature to form micelles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations